Экспериментальные исследования предела огнестойкости многослойных ограждающих конструкций с использованием магнезитовых плит - Vasilenko, А.; Rak, Т. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
An analysis of application in building sandwich panels filled with expanded polystyrene has been done. The ways to improve fire resistance of such structures was justified. The test on combustibility, flammability, flame spread ability and smoke-forming ability of magnesite slabs has been described. The use of magnesite slabs in sandwich panels for the fire protection of expanded polystyrene, where it takes effect like an insulating layer, has been prove up. The design of the proposed prototypes of sandwich panels with expanded polystyrene filler has been considered. Experimental studies of the fire resistance of proposed samples have been described. The results of experimental studies have been presented and the area of possible application of that walling type according to their fire resistance grade has been proved.